The Fulani of Abet: Research for development of agropastoralism in the West African Savannah - Waters-Bayer, Ann; Bayer, W. (1984)
Presents ILCA's research study in the subhumid zone of west Africa regarding the Fulani of Abet. Includes settlement and land use, farmer-interactions, cropping, fallow & crop residue grazing, hired labour, herd management, herd productivity, inovation design & testing, supplementary feeding, legume under sowing and fodder banks.